2021
DOI: 10.3389/fendo.2021.554604
|View full text |Cite
|
Sign up to set email alerts
|

Association of Insulin Resistance and β-cell Function With Bone Turnover Biomarkers in Dysglycemia Patients

Abstract: BackgroundThe interrelation between glucose and bone metabolism is complex and has not been fully revealed. This study aimed to investigate the association between insulin resistance, β-cell function and bone turnover biomarker levels among participants with abnormal glycometabolism.MethodsA total of 5277 subjects were involved through a cross-sectional study (METAL study, http://www.chictr.org.cn, ChiCTR1800017573) in Shanghai, China. Homeostasis model assessment of insulin resistance (HOMA-IR) and β-cell dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 40 publications
1
23
1
Order By: Relevance
“…HOMA-IR was negatively related to P1NP. They conclude that detection of bone turnover markers in diabetes or hyperglycemia patients helps to predict the risk of osteoporosis and fracture, relieve patients' pain and reduce the expenses of long-term cure (36).…”
Section: Discussionmentioning
confidence: 99%
“…HOMA-IR was negatively related to P1NP. They conclude that detection of bone turnover markers in diabetes or hyperglycemia patients helps to predict the risk of osteoporosis and fracture, relieve patients' pain and reduce the expenses of long-term cure (36).…”
Section: Discussionmentioning
confidence: 99%
“…In a study enrolling 5,277 patients with T2D, Guo et al. determined that β-cell function (as measured based on HOMA-%β) was positively correlated with BTM levels ( 29 ). Here, serum sodium levels were found to be independently related to BTMs even following adjustment for glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“… 40 Guo et al found that PINP and β-CTX levels were negatively correlated with the homeostasis model assessment of insulin resistance (HOMA-IR). 41 Hyperinsulinemia can itself trigger IR, leading to a vicious cycle of hyperinsulinemia-IR, affecting osteoclasts and osteoblasts via dysfunction of the insulin-signaling cascade. 42 , 43 High insulin levels may increase osteoclast activity, which may affect the balance of bone metabolism and thus increase the risk of fracture in patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%